Dynamic Integration Capability with Alliance Performance in Learning Framework: The Case of Strategic Alliance Performance in Learning Framework - Chrisanty, Febri Nila; Dewandaru, Janu; Mahameru, Juniar (ULTIMA Management, 2025)
In a collaborative learning environment involving strategic alliances, the process of integration is critical. The main objective of this research is to conduct a comprehensive examination of dynamic integration capabilities (relationship capital, surfacing, joint learning structure, and knowledge acquisition), particularly in the context of learning within strategic alliances. This research is to answer how the public institution can stay competitive and improve their integration capability through strategic alliances in learning area specifically. This research is groundbreaking as it is the first to empirically examine all the learning framework’s constructs, which includes relationship capital, surfacing, joint learning structure, and knowledge acquisition, in relation to dynamic integration capability and strategic alliance performance at the same time. The research utilized a quantitative method. The seven-point Likert scale survey was conducted through online to 83 respondents from 83 strategic alliances within a public institution in Indonesia from November 2023 to June 2024. Additionally, open-answered interviews with some respondents were organized to deepen the understanding of research findings. The research reveals that dynamic integration capability has a positive correlation with the performance of strategic alliances. Furthermore, it indicates that all constructs within the learning framework significantly impact dynamic integration capabilities. Among these, the construct of knowledge acquisition shows the strongest correlation with dynamic integration capability. The knowledge acquisition has the most significant impact on dynamic integration capability and suggested that public institutions and strategic alliances are effectively promoting cooperation through joint research projects and other similar activities to stay competitive. Keywords: Dynamic Integration Capability; Learning Framework; Strategic Alliance; Dynamic Capability.